Diseño de un manual de operaciones y propuesta de mejoras de proceso para la empresa OCEAN Services Y Trading S.A.S en el municipio de Socha Boyacá (2021)
The purpose of this project is to design an operations manual and create proposals for improvements in the company OCEAN SERVICES Y TRADING S.A.S in the municipality of Socha, Department of Boyacá. To achieve this, an initial diagnosis was applied that allows us to appreciate the strengths and weaknesses of the procedures applied to the International ASTM (American Society of Test Materials) standards, which will allow us to verify all administrative and operational processes. At the time of evidencing the diagnosis made, the weaknesses and strengths must be presented to the company OCEAN SERVICES Y TRADING S.A.S. The corrective and preventive actions that help the development of the didactic manual of operations and procedures, taking into account the findings found in this diagnosis such as partial non-compliance, applicable regulations, processes without procedures documented. To carry out this degree work, it was important to use research techniques focused on compliance with the standards required for each process, both operative and analytical, among which two inductive methods could be applied, because for the project, it is necessary to establish the observation of the processes of production in the company to register them, classify it and with the help of the deductive method, all the variables that control the company will be identified and analyzed, in order to establish the effects that they can cause in the Company